Planting Some Media Testing And Grant Of Supplementary Liquid Fertilizer (Ppc) On The Growth And Production Lettuce Plants (Lactuca Sativa L) Hydroponically - Rahayu, Sri '; ', Armaini '; ', Ardian ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims for knowing the influence a media types and PCC and determine the type of media and PPC is good for growth and yield of lettuce (Lactuca sativa L). The researched was carried out atscreen house Faculty of Agricultural experiment station, UR in September – November 2015 using a randomized etely design which consist of two factors and acquired 4 combination treatments with six replications, in order to obtain 24 units experiment.Parameters measured were plant height, leaf number, fresh weight, dry weight potable weight ratio canopy and roots. The results showed that the combination of provision of planting medium and the nutrient solution no real effect on all parameters. Granting planting medium husk 200 g and a nutrient solution Bayfolan 3 g / l of water to get the best results on the growth and yield of lettuce. Keywords: Lettuce, Growing medium, Nutrient solution